Cost of peripheral neuropathy in patients receiving treatment for multiple myeloma: a US administrative claims analysis. (March 2019) - Song, Xue; Wilson, Kathleen L.; Kagan, Jerry; Panjabi, Sumeet
Background: Peripheral neuropathy (PN) is a common consequence of multiple myeloma (MM) among those commonly treated with older-generation proteasome inhibitors (PIs). In this study, we evaluated the economic burden attributable to PN among MM patients in real-world practice settings in the US. Methods: Adults diagnosed with MM and first treated (index event) between 1 July 2006 and 28 February 2017 were identified from MarketScan® Commercial and Medicare claim databases. Continuous enrollment for at least 12 months without treatment and PN diagnoses were required pre-index. Patients were followed for at least 3 months until inpatient death or end of data. The International Classification of Diseases, ninth revision, Clinical Modification (ICD-9-CM) and ICD-10-CM diagnosis codes were used to identify PN. Propensity-score matching was applied to match every patient with PN to two MM patients without a PN diagnosis (controls). Healthcare utilization and expenditures per patient per month (PPPM) in the postindex period were estimated. Results: Of 11, 851 patients meeting the study criteria, 15.5% had PN. After matching 1387 patients with PN and 2594 controls were identified. Baseline characteristics were well balanced between cohorts; mean follow up was 23–26 months. PPPM total costs were significantly higher by 1509 for patients with PN than controls, driven by higher hospitalization (PN 77.4%, controls 67.2%; p < 0.001) and emergency department rates (PN 67.8%, controls 58.4%; p < 0.001) and more outpatient hospital-based visits PPPM (PN 13.5 ± 14.7, controls 11.5 ± 18.0; p < 0.001). Conclusions: PN is a prevalent MM treatment complication associated with a significant economic burden adding to the complexity and cost of MM treatment. Highly effective novel treatments such as carfilzomib may reduce the overall disease burden.